Enquête sur l'encastrement territorial des pratiques de l’économie circulaire en Région de Bruxelles-Capitale - Deborah Lambert; Mariana Santos; David Bassens (Brussels Studies, 2022)
The Circular Economy (CE) has been on the agenda of the Brussels Capital Region (BCR) as means of combining sustainability and economic Igoals like fixating productive activities in the region and job creation. This paper draws on six cases in the agro-food sector to explore how the CE is inserted in the socio-spatial, economic, cultural, financial and institutional fabric of the region. We find that the CE comprises a plurality of practices, which promises multiple avenues for CE expansion. We recommend attending to this variegation, as policies seek coalitions between the Region, firms with diverging business models and missions, and community- based initiatives in different areas. We also identify the need to value “circular jobs” and recommend heightened sensitivity to urban circular economies beyond (1) those centered on middle/high income consumer markets, and/or (2) those fueling property market value rise.